Seasonal variations among admitted paediatric patients at tertiary care hospital, Gadap Town, Karachi, Pakistan - Seema, Nighat; Khan, Hina; Jiskani, Asad. R.; Saboohi, Erum; Channa, Yasmeen; Maqsood, Syed; Tariq, Anus; Khan, Tooba (International Journal of Research in Medical Sciences, 2019)
Background: In pediatrics, the season is one of the elements contributing to the etiological factors of community based diseases. Awareness of this variation can help the physicians for prevention and counseling of the patients. A cross-sectional observational study was designed with non-probability convenient sampling technique to determine the frequency of patients admitted to the paediatric ward of the hospital in a whole calendar year and to ascertain which disease presentation is most common. Methods: Study conducted at paediatric ward of Al-Tibri Medical College and Hospital Karachi, Pakistan having patients admitted during May 2018 to April 2019. After ethical approval and informed consent from their parents/ guardian, a total of 734 paediatric patients that were admitted from paediatric OPD/ emergency were selected for the study. Paediatric patients that were referred, in emergency/ ICU and surgical paediatric patients were excluded from the study. Chi-square test was applied to evaluate the statistical variation among the patients. Results: From the 734 patients, 357 (48.6%) patients were of acute gastroenteritis, 104 (14.2%) of respiratory illness, 86 (11.7%) of viral fever, 67 (9.1%) of urinary tract infection, 36 (4.9%) of neurological illness, 29 (4.0%) of protein calorie malnutrition, 25 (3.4%) of enteric fever, 20 (2.7%) of haematological illness and 10 (1.4%) patients were admitted due to sepsis. Conclusion: Our study concluded that majority of the patients admitted were of acute gastroenteritis / admitted due to gastric issues, therefore further studies in the vicinity would help to better understand the issues and help plan a strategy to combat the diseases.